Computational analysis of conductive fluid flow with tangential components of magnetic flux density and electric field in metallic and non-metallic circular pipe. Issue 1 (31st December 2023) - Vadde, Anusha; Kadambi, Govind R; C, Siddabasappa
Abstract: This paper has focused on the study of flow characteristics of a steady conductive fluid through a circular pipe in the presence of an applied transverse uniform magnetic field. A numerical simulation of the fluid flow was performed using a multi-physics computational tool. The radial velocity distribution due to the effect of the tangential component of induced magnetic flux density and electric fields at various axial positions is examined in metallic and non-metallic surfaces of the circular pipe. This simulation study helps to analyse the effect of drag force on the variation in axial velocity close to the metallic and non-metallic walls. The induced electric potential is directed along the normal to the Laplacian tangential surface of the pipe. In addition to that, sigmoidal-shaped field profiles are observed when the fluid flow crosses from the upstream to downstream of the magnet edge and vice versa along the axial length of the circular pipe. Simultaneously, it is observed that the average velocity of the fluid flow decreases for a laminar and increases for turbulent Reynolds number. Streamline plots pertinent flow variable such as flow velocity are presented for non-conducting and conducting walls.